Ipsilateral Acetabular Fracture with Displaced Femoral Head and Femoral Shaft Fracture: A Complex Floating Hip Injury - Raja Bhaskara Rajasekaran; Dheenadhayalan Jayaramaraju; Dhanasekara Raja Palanisami; Ramesh Perumal; Rajasekaran Shanmuganathan (Case Reports in Orthopedics, 2018)
Floating hip injuries involving the acetabulum, femoral head, and the femoral shaft are a very rare presentation. A complex floating hip injury comprising of an ipsilateral acetabular fracture associated with a displaced femoral head fracture and a femoral shaft fracture following a high-velocity road traffic accident presented to us where all the fractures were addressed with internal fixation during the primary surgery. Postoperatively, the patient suffered a dislocation of the femoral head which eventually went on to avascular necrosis at 5 months from the initial presentation. Then, the patient underwent a total hip replacement with an acetabular reconstruction following which he went on to have a good functional outcome. Our experience in dealing with such a complex case shows that it is difficult to set a protocol for such injuries and they need to be addressed on a case-to-case basis depending on the complexity of the injury.